Impact of Intranasal Corticosteroids on Intraocular Pressure and Retinal Nerve Fiber Layer Thickness: A Cross-Sectional Study at a Tertiary Care Hospital in Pakistan - Saira Bano, Abdul Haleem, Rehan Moinuddin Shaikh, Maqsood Ahmed, Ahsan Qureshi, Javed Iqbal (Pakistan Journal of Medical & Health Sciences, 2024)
Background: A worldwide health concern, rhinitis affects 10% to 20% of Pakistan’s population. For extended periods of time, otolaryngologists frequently treat patients with rhinitis with topical intranasal corticosteroids (INCS). While oral corticosteroids have well-established effects on intraocular pressure (IOP) and lens opacity, the effects of INCS are less clear. In this study, we sought to determine how utilizing INCS affected individuals with rhinitis’s intraocular pressure during a six-month period. Objective: This study aimed to assess the impact of long-term INCS use on IOP and Retinal nerve fiber layer (RNFL) thickness. Methods: This cross-sectional study was conducted at a tertiary care hospital in Pakistan. Patients using INCS for at least six months were recruited and compared with a control group of non-users. IOP was measured using Goldmann applanation tonometry, while RNFL thickness was assessed via optical coherence tomography (OCT). Demographic and clinical data were recorded. Statistical analysis included independent t-tests and Pearson correlation to evaluate associations between INCS use, IOP, and RNFL thickness. Results: A total of 112 participants (56 corticosteroid users and 56 non-users) were included. IOP was significantly higher in corticosteroid users (16.8 ± 2.3 mmHg) than in non-users (14.2 ± 1.8 mmHg) (p < 0.001). RNFL thickness was significantly reduced in corticosteroid users (91.4 ± 6.7 µm) compared to non-users (98.6 ± 5.9 µm) (p < 0.001). A slight +ve correlation was observed between the duration of intranasal corticosteroid use and IOP in the left eye (r = 0.251, p = 0.019), but non-significant correlation was seen with RNFL thickness. Conclusion: Prolonged INCS use may contribute to increased IOP and localized RNFL thinning, suggesting a potential risk for glaucomatous changes. Routine ophthalmic monitoring is recommended for chronic INCS users, particularly those with predisposing risk factors for glaucoma. Keywords: Intranasal corticosteroids, intraocular pressure, retinal nerve fiber layer, glaucoma risk, optical coherence tomography.